2000
DOI: 10.1046/j.1440-1746.2000.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐steroidal anti‐inflammatory drugs with different cyclooxygenase inhibitory profiles that prevent aberrant crypt foci formation but vary in acute gastrotoxicity in a rat model 1

Abstract: Cyclooxygenase-2 inhibitors are potentially ideal chemopreventive agents as they inhibit ACF and are not gastrotoxic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…ACFs are considered to be an early preneoplastic lesion in the colon (75), and the ability to decrease the frequency of ACF after carcinogen treatment is used routinely in experimental models of colon cancer to estimate the cancer preventive effect of different agents (76). It is particularly well established that NSAIDs (77)(78)(79) and celecoxib (80)(81)(82)(83) decrease the frequency of carcinogen-induced ACFs in the colon in animal models. It has also been shown that the number of ACF in patients who received sulindac sulfide is decreased (84).…”
Section: Discussionmentioning
confidence: 99%
“…ACFs are considered to be an early preneoplastic lesion in the colon (75), and the ability to decrease the frequency of ACF after carcinogen treatment is used routinely in experimental models of colon cancer to estimate the cancer preventive effect of different agents (76). It is particularly well established that NSAIDs (77)(78)(79) and celecoxib (80)(81)(82)(83) decrease the frequency of carcinogen-induced ACFs in the colon in animal models. It has also been shown that the number of ACF in patients who received sulindac sulfide is decreased (84).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that nonsteroidal anti-inflammatory drugs, and particularly celecoxib, decrease the frequency of ACF in humans as well as in rodent models of carcinogen-induced colon cancer (67)(68)(69)(70). We compared the changes in gene expression found in normal descending colonic mucosa of patients treated with celecoxib for 1 year (71) to the differences seen in gene expression between ACF and NM from the descending colon.…”
Section: Discussionmentioning
confidence: 99%
“…These include sulindac, indomethacin, piroxicam, aspirin, and ibuprofen, and the selective COX-2 inhibitors celecoxib, rofecoxib, nabumetone and meloxicam. [32][33][34]38,[46][47][48]53,54,66,67,74,[120][121][122] A dosedependent effect of NSAIDs and COX-2 inhibitors exists against both the initiation and promotion of the adenoma-carcinoma sequence, and pre-existing tumors. Of note, there are regional differences in sensitivity for chemopreventive treatment.…”
Section: Lessons From Animal Modelsmentioning
confidence: 99%